2019
DOI: 10.3892/or.2019.7267
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of organic cation transporter 3 in oxaliplatin treatment of colon cancer in vitro and in vivo

Abstract: Oxaliplatin (OXA) is routinely used as the first-line treatment for colorectal cancer (CRC). The addition of OXA to chemotherapy has significantly improved the prognosis of patients with CRC; however, some cases are resistant to OXA. The present study explored the influence of organic cation transporter 3 (OCT3) expression on the effects of OXA on CRC cell viability, and investigated the direct effects of OCT3 on viability, invasion and migration of CRC cells using MTT assay, wound healing assay, reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Notably, among numerous DEGs shown to be specifically expressed, or significantly enriched, either in brain BVs (brBVs) or in sciatic nerve BVs (snBVs), our analysis revealed the selective expression of some transporters responsible for the uptake of a chemotherapeutic drug, oxaliplatin, in brBVs or snBVs. Indeed, as for other platinum salts used as anti-cancer drugs known to cause a common and dose-limiting peripheral neuropathy, several transporters localized to the cell membrane of dorsal root ganglion were associated with oxaliplatin uptake and efflux across the plasma membrane: the organic cation transporters OCT2, OCT3 and OCTN1/2, as well as the copper transporter CTR1 were described to be preferentially involved in oxaliplatin uptake while copper P-type ATPase ATP7B as well as multidrug resistance-associated protein 2 (MRP2) and multidrug and toxin extrusion protein 1 (MATE1) would mediate the efflux of oxaliplatin (Fujita et al, 2019; Gu et al, 2019; Cheng et al, 2023). Given that oxaliplatin treatment exclusively affects the peripheral nervous system, we searched for any selective expression of these transporters in snBVs, which could underlie the pathogenesis of OIPN.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, among numerous DEGs shown to be specifically expressed, or significantly enriched, either in brain BVs (brBVs) or in sciatic nerve BVs (snBVs), our analysis revealed the selective expression of some transporters responsible for the uptake of a chemotherapeutic drug, oxaliplatin, in brBVs or snBVs. Indeed, as for other platinum salts used as anti-cancer drugs known to cause a common and dose-limiting peripheral neuropathy, several transporters localized to the cell membrane of dorsal root ganglion were associated with oxaliplatin uptake and efflux across the plasma membrane: the organic cation transporters OCT2, OCT3 and OCTN1/2, as well as the copper transporter CTR1 were described to be preferentially involved in oxaliplatin uptake while copper P-type ATPase ATP7B as well as multidrug resistance-associated protein 2 (MRP2) and multidrug and toxin extrusion protein 1 (MATE1) would mediate the efflux of oxaliplatin (Fujita et al, 2019; Gu et al, 2019; Cheng et al, 2023). Given that oxaliplatin treatment exclusively affects the peripheral nervous system, we searched for any selective expression of these transporters in snBVs, which could underlie the pathogenesis of OIPN.…”
Section: Discussionmentioning
confidence: 99%
“…The transport via OCTs is facilitative and Na + - and Cl − -independent, occurring in both direction across the plasma membrane based on the electrochemical gradient of the transported substrates [ 74 , 93 , 174 , 175 ]. A variety of anticancer drugs have been identified as OCT transporter substrates, and several of them are listed in Table 1 [ 66 , 71 , 72 , 73 , 76 ]. OCT1/SLC22A1 is mainly expressed on the sinusoidal membrane of hepatocytes, and was detected in the small intestine, renal proximal tubular cells, the brain (neurons and endothelial cells of the blood–brain barrier), the heart, skeletal muscle, the lungs, adipose tissue and immune cells [ 67 , 68 ].…”
Section: Slc Transporters In Cancermentioning
confidence: 99%
“…On the other hand, some members of the SLC family 22 shown to be involved in the uptake of platinum compounds have been more directly linked to drug efficacy. For example, in a retrospective study Gu et al [20] found that high expression of SLC22A3 (OCT3) may be a protective factor for CRC patients postoperatively treated with FOLFOX6 as a first-line adjuvant chemotherapy. In line with this, the same group also demonstrated in in vitro and in vivo experimental systems that the cellular concentration of oxaliplatin and its cytotoxicity were significantly increased in response to high expression of OCT3, whereas OCT3 knockdown directly increased the invasion and migration of colon cancer cells.…”
Section: Tymsmentioning
confidence: 99%
“…In line with this, the same group also demonstrated in in vitro and in vivo experimental systems that the cellular concentration of oxaliplatin and its cytotoxicity were significantly increased in response to high expression of OCT3, whereas OCT3 knockdown directly increased the invasion and migration of colon cancer cells. In addition, upregulation of OCT3 expression in colon cancer xenografts via treatment with the DNA methyltransferase inhibitor decitabine increased the cellular concentration of the drug and improved its curative effect [ 21 ] . Key mediators for oxaliplatin accumulation inside the cells are also a series of proteins initially identified as copper transporters.…”
Section: Resistance To Chemotherapymentioning
confidence: 99%